2013
DOI: 10.1097/mbp.0b013e3283651d19
|View full text |Cite
|
Sign up to set email alerts
|

Increased echocardiographic epicardial fat thickness and high-sensitivity CRP level indicate diastolic dysfunction in patients with newly diagnosed essential hypertension

Abstract: In patients with newly diagnosed and untreated essential HT, increased EFT thickness and hs-CRP level are significantly related to impaired LV diastolic function independent from other factors, including age, waist circumference, and 24-h systolic blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
(49 reference statements)
5
19
1
1
Order By: Relevance
“…21 The CRP level in hypertensive patients with left ventricular dysfunction was found to be higher than the others. 25,26 Despite normal levels in the WCH and HT groups, compared with the NT group, CRP and ESR levels in the HT group and CRP levels in the WCH group were significantly higher. It was declared that the increase in CRP levels was accompanied with an increase in CIMT, as the period of the disease increased.…”
Section: Discussionmentioning
confidence: 73%
“…21 The CRP level in hypertensive patients with left ventricular dysfunction was found to be higher than the others. 25,26 Despite normal levels in the WCH and HT groups, compared with the NT group, CRP and ESR levels in the HT group and CRP levels in the WCH group were significantly higher. It was declared that the increase in CRP levels was accompanied with an increase in CIMT, as the period of the disease increased.…”
Section: Discussionmentioning
confidence: 73%
“…Epicardial fat serves a number of important physiologic functions including acting as a buffer for coronary arteries against torsion, regulation of fatty acid metabolism for coronary arteries, thermogenesis, and protection of the cardiac autonomic ganglia and nerves . The association of increased epicardial fat with diastolic dysfunction has been consistently demonstrated in various studies . A recent meta‐analysis of studies using relatively simple indicators of diastolic dysfunction, mitral valve E/A ratio or E/e′, showed a significant correlation between the amount of epicardial fat and diastolic dysfunction (Figure ).…”
Section: Epicardial Fatmentioning
confidence: 96%
“…EAT has received much attention recently due to its metabolically active nature and relation with several bioactive adipokines [1-4]. Studies have shown an association between EAT and traditional cardiovascular risk factors, coronary atherosclerosis, coronary artery plaque burden, and major adverse cardiovascular events [5-7].…”
Section: Introductionmentioning
confidence: 99%